A real-time surveillance mini-rover based on OpenCV-Python-JAVA using Raspberry Pi 2 - Hossain, Nazmul; Kabir, Mohammad Tanzir; Rahman, Tarif Riyad; Hossen, Mohamed Sajjad; Salauddin, Fahim (2015 IEEE International Conference on Control System, Computing and Engineering (ICCSCE), 2015)
Real-time surveillance is a vital component in any situation or environment where there is a high need of security for both personal and commercial property and assets. Technology today is used in many different ways in order to provide us such surveillance. An ideal solution for surveillance involves not only the assortment of necessary sensors and devices using appropriate tools, but also should be provided in the most optimized way for obtaining feed and data while keeping the expenditure minimized. In our project, we aimed at developing a low-cost, real-time video surveillance mini-rover which will be capable of providing real-time video footage and roam around in the area which we want to observe. Our target was to use hardware which is very low of cost and easily available.